Improved Watermark Criteria Through Mark image - Abdulkreem Mohammed Salih; Karam M.Z. Othman; Shayma Wail Nourildean (NTU Journal of Engineering and Technology)
With many applications using digital multimedia technologies, the need to protect digital multimedia data from hackers is emphasized. Copyright holders are concerned about protecting any kind of unlawful duplication of their information. With all these kinds of problems, technology development is very important. Digital watermarks are an important requirement to protect multimedia data. There are important criteria to measure the success of a watermarking process, it is confidentiality, capacity and reliability. In this paper, the logo mark was relied upon to achieve these criteria to a high degree by taking advantage of the symmetry characteristic of the logo image, Which is often used this type of logo  images. Symmetry reduces the size of the embedded data, reduces the location of the embedded within the image, and increases confidentiality by encrypting less data in various ways.